2018
DOI: 10.1097/rlu.0000000000002187
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Serial FDG PET/CT During Treatment of Extrapulmonary Tuberculosis in HIV-Infected Patients

Abstract: In difficult-to-treat entities such as extrapulmonary TB in HIV patients, FDG PET/CT is a potential tool in monitoring TB treatment response and should be explored in larger studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…18F-fluorodeoxyglucose Positron Emission Tomography (18F-FDG-PET) is not routinely used; while it can identify sites of active inflammatory disease, it cannot differentiate GUT from cancer [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…18F-fluorodeoxyglucose Positron Emission Tomography (18F-FDG-PET) is not routinely used; while it can identify sites of active inflammatory disease, it cannot differentiate GUT from cancer [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…It should be noted, however, that detection of extrapulmonary lesions may be particularly useful in such patients since they could be due to a variety of infectious or noninfectious complications of HIV/AIDS. The role of 18 F-FDG PET/CT in HIV-infected patients was recently addressed in a small study of 18 HIV/TB patients [15]. After 2 months of treatment, 78% of patients had a significant metabolic response.…”
Section: Discussionmentioning
confidence: 99%
“…Positron emission tomography (PET) using 2-deoxy-2-[fluorine -18] fluoro-D-glucose ( 18 F-FDG) provides functional information on sites of active inflammation and, in combination with CT data, delivers functional and anatomical information in a single scan [8,9]. Preliminary studies on TB in macaques [10][11][12][13] and humans [14][15][16][17][18][19] employing 18 F-FDG PET/CT as a research tool have suggested that it might be of clinical value for localisation of disease sites and assessment of treatment response. Currently there are several ongoing research studies on the application of PET/CT as a biomarker of treatment response in new drug combination trials and for insight into pathogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…On autopsy, multiple tuberculous lesions may be detected throughout the body in organs such as the lungs, liver, spleen, brain and others. There are many studies and case reports relevant to PET/CT utility that reveal the diagnostic and the thera-peutic response evaluation in tuberculosis patients [9][10][11][12][13][14][15][16][17][18][19][20][21]. These studies are about the organ involvement of mycobacterium tuberculosis infection while none of these papers have presented data concerning miliary tuberculosis.…”
Section: Discussionmentioning
confidence: 99%